The People’s Regulation: Citizens and Implementation of Law in China - Rooij, Benjamin van (Columbia Journal of Asian Law, 2012)
China has made a move towards society-based regulation, enabling citizens to aid in the implementation of regulatory law. This is a welcome development that may help to reduce the government’s problems in enforcing its laws. Societal forces have also had some success in improving regulatory efforts to mitigate risk. However, society-based regulation reforms have been halfhearted, as existing and recently introduced authoritarian restrictions obstruct citizens from becoming successful co-regulators. At its worst, China has developed a form of regulation by escalation, where ironically the exact same incentive structures for Chinese regulatory and judicial officials to prevent unrest also stimulate citizens to create instability as a successful strategy to get regulatory law implemented. And thus, China’s halfhearted approach to regulatory governance with its focus on stability may ultimately be destabilizing.